Pengaruh Perubahan Nilai Koefisien Dasar Bangunan (KDB) Terhadap Peningkatan Debit Air Limpasan (Run Off) Pada Kawasan Perumahan Di Kelurahan Meteseh, Kecamatan Tembalang - Putri Mutiara Bena; Parfi Khadiyanta (Jurusan Perencanaan Wilayah dan Kota, 2020)
Meteseh included in one of the flood-prone areas in the city of Semarang. One of the causes of flooding in Meteseh is the high discharge of runoff water that goes to the river so that the river cannot accommodate the amount of water it should have and floods occur. Besides, the high flow of runoff water can also be influenced by changes in the value of the basic building coefficient (KDB). KDB is a percentage comparison of the area of a house with the floor area of the building that stands on it. KDB rules are set to limit so that the lots are not completely covered by pavement. It is intended that the lot can provide open space that can function as a greening and catchment area. But in reality, there are still many people who have not obeyed this regulation. Therefore, this study aims to look at the effect of changing KDB values on the increase in runoff water in residential areas in Meteseh, Tembalang District. This research uses quantitative methods, where data collection techniques are carried out by field observation methods and the distribution of questionnaires to 100 samples using multistage random sampling techniques in developer housing and ordinary housing. The results of this study note that the KDB change of 274 m2 in housing developers can increase runoff water flow by 7% (388.62 m3/yr) and KDB change of 340 m2 in ordinary housing can increase runoff water flow by 6% (482, 23 m3/yr).